Is the grazing tolerance of mesic decreaser and increaser grasses altered by soil nutrients and competition?. Issue 4 (1st October 2016) - Morris, Craig D
Abstract : An ability to tolerate recurrent defoliation likely plays a role in the compositional shift from decreaser to increaser species with overgrazing of mesic grassland, but the grazing tolerance of local species has not been extensively studied. The growth response of two decreasers, three Increaser II grasses, and an Increaser III species to frequent, severe defoliation under three levels of competition from neighbours and two levels of soil nutrients was examined in a pot trial. The effects of competition and especially nutrients markedly modified the defoliation tolerance of different species, and grazing response groups varied in the manner in which their defoliation responses were mediated by these interactions. Contrary to expectation, defoliation constrained potential productivity most in nutrient-rich, competition-free environments, probably because it exacerbates a carbon limitation on growth. However, nutrient enrichment did enable Increaser II grasses, but not other species, to better tolerate intense defoliation, explaining why they can persist on intensively grazed fertile patches and in heavily stocked grassland, such as in communal areas, where nutrients are more available. It is concluded that grazing tolerance is not a fixed property of species or grazing response groups but depends on biotic and abiotic environmental factors.